Including Stakeholder Intent in Precinct Information Models. (2017) - Marchant, David; Plume, Jim
Abstract: Planning, building, and occupying a precinct, involves many stakeholders over significant periods of time. The development and evolution of the precinct is determined through decisions made by these stakeholders, jointly or singly, in response to perceived existing problems, or to satisfy anticipated future needs. The stakeholders are therefore all participating in an ongoing "design" process for the precinct. The current state of the precinct (its physical, social, psychological "fabric") at any given time is a result of their cumulative decisions. However, the dynamic that drives the evolution of the precinct is expressed through stakeholder indicators of future intent (stated problems and/or aspirational visions). Stakeholders come and go over the lifetime of a precinct. Their interests in, and perspectives regarding, the precinct vary, which means that the information they require or generate about the precinct also varies. Additionally, the software they use varies, so information has tended to remain in separate repositories (financial, urban planning, building design, and other specialities) This disaggregation of interest over time can lead to losses of information, miscommunication between stakeholders, and ultimately to a lack of any shared meaning about the precinct especially if the intent of stakeholders that has driven decisions is not retained. The ongoing Precinct Information Modelling research project within the CRC for Low Carbon Living seeks to address the issue of information sharing for precincts. This paper describes the data entities defined in the author's own research on design briefing that now have been appended to the proposed standardised PIM data schema to allow for this perceived need to integrate stakeholder intent.